Stability of Odd‐ Versus Even‐Electron Gas‐Phase (Quasi)Molecular Ions Derived from Pyridine‐Substituted N‐Heterotriangulenes. Issue 2 (22nd November 2016) - Hitzenberger, Jakob F.; Dral, Pavlo O.; Meinhardt, Ute; Clark, Timothy; Thiel, Walter; Kivala, Milan; Drewello, Thomas
Abstract: Electrospray ionisation of N‐heterotriangulenes (i.e., dimethylmethylene‐bridged triphenylamines) with up to three pyridyl groups at their periphery, produces the true radical cation ([ M ] + . ) and the protonated molecule ([ M +H] + ) simultaneously. These ions are studied as model systems to illustrate the stability alternation of odd‐ versus even‐electron ions in energy‐dependent collision‐induced dissociation (CID) experiments. All ions show the same fragmentation pattern, the consecutive loss of three methyl radicals ( . CH3 ) from the dimethylmethylene bridges of the central triangulene core. [ M ] + . ions dissociate at much lower collision energies than their [ M +H] + counterparts. The radical cation forms a singlet fragment with an extended aromatic system that is energetically favoured. Ab initio and density functional theory calculations support this interpretation and allow the assignment of the electronic structure of the fragment ions. Consecutive collision‐induced dissociations provide a better match with theory when studied with an ion trap, rather than a linear quadrupole. This is attributed to the resonant nature of the excitation of intermediate ions. Abstract : Odd‐ vs. even‐electron ion stability check : The true radical cation ([ M ] + . ) of N‐heterotriangulenes dissociates at much lower collision energies than the protonated molecule ([ M +H] + ) in gas‐phase collisions (see figure). [ M ] + . forms a singlet with extended π‐system that is energetically favoured. Ab initio and DFT calculations support this interpretation and allow the assignment of the electronic structure of the fragment ions.